Alsace and Burgundy : Spatial Patterns in the Early Middle Ages, c. 600-900 - Karl Weber (Bulletin du Centre d’Études Médiévales d’Auxerre)
This paper examines the long-term spatial concepts in today’s Northern Switzerland, in the north-east of Burgundy and in Alsace during Merovingian and Carolingian times (ca. 600-900). As a result of the examination of the words pagus and ducatus in the sources, it seems clear that the dukes of the Merovingian era in our region ruled on pagi, not duchies. However, Alsace formed a core area of the Austrasian regnum on the left side of the Upper Rhine Valley. In the late Merovingian period the dukes of Alsace received the authority over the former Burgundian parts in the Jura region. The introduction of the spatial concept ducatus in Alsace was an innovation acted under Louis the Pious (814-840). The ducatus Alsacensis was a duchy without a duke. The close relationship between the southern parts of Alsace and the former Burgundian parts were also maintained later. In 10th century, the landscape discussed here became the nucleus of the Rudolphian regnum Jurense.